Expert System in Determining the Quality of Superior Gourami Seed Using Forward Chaining-Based Websites - Sivaram M.; Bazeer Ahamed B.; Yuvaraj D.; Manikandan V.; Karlus N.G.; Sitanggang A.S.; Latif A.A.; Maseleno A. (Springer Verlag, 2023)
Advanced Analytics; Big data; Expert systems; Fish species; Forward chaining; Gourami; Indonesia; Market demand; Southeast Asia; Stable prices; Fish